The keystone advantage what the new dynamics of business ecosystems mean for strategy, innovation, and sustainability - Iansiti, Marco, 1961-; Levien, Roy. (Boston : Harvard Business School Pub., 2004)
Annotation.
Title from title screen.
Includes index.
Print version record.
Added to collection customer.56279.3 - Master record variable field(s) change: 072
Keywords: Strategic planning; Business enterprises -- Technological innovations; Organizational effectiveness; Business enterprises -- Technological innovations; Organizational effectiveness; Strategic planning; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books